2021
DOI: 10.1017/flo.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale structures of wall-bounded turbulence in single- and two-phase flows: advancing understanding of the atmospheric surface layer during sandstorms

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 164 publications
0
9
1
Order By: Relevance
“…1979; Dharmarathne et al. 2016; Zhang, Hu & Zheng 2018; Chowdhuri, Todekar & Prabha 2021; Liu & Zheng 2021) that are similar to structures in the velocity field. Studying the influence of the fluid on the discrete particle phase and then revealing its structural characteristics in the high-Reynolds-number particle-laden wall-bounded turbulence can not only provide in-depth information on the transport behaviour of the fluid with respect to the particle but can also help to further reveal the physical mechanism of particle–turbulence interactions.…”
Section: Introductionmentioning
confidence: 95%
“…1979; Dharmarathne et al. 2016; Zhang, Hu & Zheng 2018; Chowdhuri, Todekar & Prabha 2021; Liu & Zheng 2021) that are similar to structures in the velocity field. Studying the influence of the fluid on the discrete particle phase and then revealing its structural characteristics in the high-Reynolds-number particle-laden wall-bounded turbulence can not only provide in-depth information on the transport behaviour of the fluid with respect to the particle but can also help to further reveal the physical mechanism of particle–turbulence interactions.…”
Section: Introductionmentioning
confidence: 95%
“…A detailed description of the geographic, meteorological and instrument configuration conditions at the QLOA site is given in our previous works (e.g. Zheng 2013;Zhang & Zhou 2020;Liu & Zheng 2021).…”
Section: Descriptions Of the Datasetsmentioning
confidence: 99%
“…It is shown that the effect of cloth not only enhances the average value of instantaneous wind speed, but also causes the probability of strong wind to increase in the distribution of instantaneous wind speed. While depending on the fluttering mode of the cloth, the quasiconvective turbulence has coherent structures as observed in convective ABLs (Liu and Zheng, 2021). As our main interest is how convective eddies affects aeolian particle entrainment, we did not study the intrinsic mechanisms of how cloth induces large eddies.…”
Section: Forced Perturbationmentioning
confidence: 99%